Proinflammatory Activation of Osteoclasts Due to High Prolactin Level - Saeed , Zeayd Fadhil; Kadhim, Baleegh A; Al-Yasari , Ali Mosa Rashid; Kheder , Ramiar K.; Abdulhussein , Sura Ali; James, Hobkirk; Alsaadawi , Mohenned A. (Iraqi Journal of Science, 2022)
High concentrations of prolactin (PRL) during the lactation period have an essential role in milk production by mammary glands stimulation. PRL may have an impact on calcium regulation and bone mineral density. We investigated if the PRL concentration during the lactation period could influence osteoclast (OC) activation and bone mineral density (BMD). In vivo, the Calcium Detection Assay, and ELISA were used to detect serum calcium, PRL, and inflammatory cytokines, respectively. BMD was evaluated by µ-CT in six months old female mice during lactation. The osteoclast (OC) activity was detected by Tartrate-resistant acid phosphatase (TRAP), Immunohistochemistry (IHC), and hematoxylin and eosin (H&E). In vitro, osteoclast differentiation, resorption and their activity markers TRAP, Matrix metallopeptidase 9 (MMP-9), Cathepsin K (CTSK), C-reactive protein (CRP), Receptor activator of nuclear factor kappa-Β (RANK) and inflammatory cytokines were measured in osteoclasts stimulated with recombinant prolactin protein (rPRL) or with an anti-prolactin blocker. We found that serum calcium, PRL, and inflammatory markers were increased. BMD was significantly reduced in lactating mice; TRAP activity was increased and tubercular was reduced in lactating mice compared to normal mice. In vitro, the osteoclast number, resorption, and activation markers TRAP, MMP-9, CTSK, CRP, and RANK were significantly increased after treatment with rPRL protein, but not in osteoclasts treated with anti-prolactin receptor antibody and rPRL. The gene expression of TNF-α, IL-6, and Monocyte chemoattractant protein-1 (MCP-1) but not IL-1b were significantly increased in osteoclasts with PRL treatment compared to the untreated osteoclasts. Taken together, the high level of PRL could activate osteoclasts and proinflammatory cytokines expression which reduce BMD in the lactation period.